Contested city municipal politics and the rise of Nazism in Altona, 1917 - 1937 - McElligott, Anthony 1955- (Univ. of Michigan Press, 1998)
In the wake of the First World War, many Germans saw the future of their nation as contingent on a vision of municipal progress. In this well-researched study, Anthony McElligott uses local politics as an analytical tool to decipher the bigger picture of the fare of the Weimar Republic. Focusing on the industrial city of Altona, McElligott locates his discussion of the contradictions of the Weimar "local state" along two axes - first, persistent financial, policy, and political conflict between the central and the local state and, second, the conflicts within the Weimar local state between the displaced and resentful middle classes and the newly enfranchised working class. McElligott probes beneath the level of formal party conflicts to reconstruct the "politics of everyday life" at the street level. This study will be of wide interest to historians and political scientists.
Keywords: Brauer, Max; Geschichte 1917-1937; Lokale politiek; Nationaal-socialisme; Nationalsozialismus; Sozialdemokratische Partei, Kommunalpolitik; Politik; Municipal government -- Germany -- Hamburg; National socialism -- Germany -- Hamburg; Political parties -- Germany -- Hamburg; Kommunalpolitik; Altona; Deutschland; Hamburg (Germany) -- Politics and government; Hamburg-Altona (Hamburg, Germany) -- Politics and government